(untitled) (Journal of actual problems of jurisprudence, 2016)
In this article the authors discuss cruelty against animals as an indicator of occurrence of domestic violence. In addition, the authors examine cruel behavior towards pets as a form of psychological violence per se against the persons who have an affective attachment to those animals. Statistic data confirm the existence of such connections between animal abuse and domestic violence. The authors point out that the existing legal mechanisms for the prevention of domestic violence – in the domains of family law, criminal law, and administrative law – are of limited efficacy. The authors formulate a recommendation to improve those mechanisms by raising awareness of the role of cruelty against pets as a symptom of the occurrence of domestic violence.